Gambaran kadar kreatinin serum pada pasien penyakit ginjal kronik stadium 5 non dialisis - Alfonso, Astrid A.; Mongan, Arthur E.; Memah, Maya F. (Universitas Sam Ratulangi, 2016)
Abstract: Chronic kidney disease is a pathophysiology process with various etiology, causing a progressive decline on kidney function, and in general ends with kidney failure (stage 5). For the last forty years, creatinine serum had been the most common and affordable detection serum to measure kidney performance. The amount of creatinine serum is increased on non-dialysis chronic kidney disease patients. Approximately, 57% of non-dialysis chronic kidney disease patients have 7-12 mg/dL creatinine level. Research objective: To understand the description of creatinine serum level on non-dialysis chronic kidney disease patients. Research method: Cross sectional descriptive, to obtain the data of creatinine serum on non-dialysis chronic kidney disease patients carried out on December 2015 – January 2016 at two hospitals, which are RSUP. Prof. Dr. R. D. Kandou Manado and Rumah Sakit Advent Manado. The research sample were the blood sample from 35 people suffering a stage five non dialysis chronic kidney disease, which determined by consecutive sampling from non-probability sampling model. Result: Based on the laboratory result, the 35 patients diagnosed with a stage five non dialysis chronic kidney disease are undergoing an increase on creatinine serum (100%). Conclusion: Based on the research result, it can be concluded that the increase of creatinine level is occurred on stage five non dialysis chronic kidney disease patients.Keywords: creatinine serum, stage five chronic kidney disease, non-dialysis.Abstrak: Penyakit ginjal kronik adalah suatu proses patofisiologi dengan etiologi yang beragam, mengakibatkan penurunan fungsi ginjal yang progresif, dan pada umumnya berakhir dengan gagal ginjal (stadium 5). Selama 40 tahun terakhir, kreatinin serum telah menjadi petanda serum paling umum dan murah untuk mengetahui fungsi ginjal. Kadar kreatinin serum meningkat pada pasien gagal ginjal non dialisis. Sekitar 57% dari pasien gagal ginjal non dialisis memiliki kadar kreatinin 7-12 mg/dL. Tujuan Penelitian: untuk mengetahui gambaran kadar kreatinin serum pada pasien penyakit ginjal kronik stadium 5 non dialisis. Metode Penelitan: deskriptif cross sectional, untuk mendapatkan data tentang kadar kreatinin serum pada pasien penyakit ginjal kronik stadium 5 non dialisis yang dilakukan sejak Desember 2015-Januari 2016 di dua rumah sakit yaitu RSUP. Prof. Dr. R. D. Kandou Manado dan Rumah Sakit Advent Manado. Sampel penelitian adalah sampel darah dari 35 orang yang menderita penyakit ginjal kronik stadium 5 non dialisis ditentukan dengan cara non-probability sampling jenis consecutive sampling. Hasil: Berdasarkan hasil pemeriksaan laboratorium yang dilakukan, terdapat 35 pasien yang terdiagnosis penyakit ginjal kronik stadium 5 non dialisis mengalami peningkatan kadar kreatinin serum (100%). Simpulan: Dari hasil penelitian dapat disimpulkan bahwa terjadi peningkatan kadar kreatinin serum pada pasien penyakit ginjal kronik stadium 5 non dialisis.Kata kunci: kreatinin serum, penyakit ginjal kronik stadium 5, non dialysis